Studi Literatur Karakteristik Fisik dan Mekanik Aspal Modifikasi Berdasarkan Hasil Uji Laboratorium (Periode 2020–2025) - Wenny Herdianti; I Wayan Putra Jayantara Jayantara; Arrisha Anggarini; Ivana Christine Sembiring Brahmana; Melvi Maulita Napitupulu; A. Daniel Anderson Munthe (JURNAL TECNOSCIENZA, 2026)
Conventional asphalt still has limitations in withstanding increasing traffic loads and environmental influences, which can lead to permanent deformation, cracking, and a reduction in pavement service life. Various studies have developed modified asphalt to improve pavement performance; however, the findings remain scattered and have not been comprehensively synthesized. This study aims to examine the physical and mechanical characteristics of modified asphalt based on laboratory testing results using the Systematic Literature Review (SLR) method. Data were collected from Google Scholar, ScienceDirect, SpringerLink, ResearchGate, and SINTA-indexed national journals published between 2020 and 2025. The initial search yielded 85 articles, and after applying the inclusion and exclusion criteria, 11 articles were selected for analysis. The reviewed data included binder physical characteristics, rheological properties, and the mechanical characteristics of asphalt mixtures. The results indicate that the use of modification materials such as polymers, rubber, nanomaterials, and plastic waste generally improves the softening point, Marshall stability, and resistance to permanent deformation. However, the increased stiffness observed in some modified asphalt types may reduce mixture flexibility and increase the risk of cracking at low temperatures. Therefore, modified asphalt has significant potential to enhance pavement performance, but the selection of modification materials and their dosage should be adjusted to technical requirements to achieve optimal performance.